Detection of Hepatitis B Surface Antigen among Febrile Patients in Ankpa, Kogi State, Nigeria. (11th February 2020) - Omatola, Cornelius Arome; Onoja, Bernard Anyebe; Agama, Joseph
Abstract : Background . Hepatitis B virus (HBV) infection has become a significant public health problem in developing countries, and the high rate of morbidity and mortality from acute and chronic infections is worrisome. Therefore, this study determined the prevalence of HBV and associated risk factors in Ankpa, Kogi State, Nigeria. Materials and Methods . Sera randomly collected from 200 participants in three public hospitals in Ankpa were screened for HBsAg using commercially available HBsAg rapid test kit (Swe-Care (R), China). Structured questionnaires were used to obtain sociodemographic details and history of exposure to risk factors. Results . Seventeen (8.5%) of the 200 patients were positive for HBsAg. Males had higher prevalence (10.89%) than females (6.06%). The age group with the highest rate of infection was 24–44 years. Patient's occupation and marital status were significantly higher in relation to HBsAg seropositivity. Risks of HBV infection in Ankpa are sharing of sharp objects (OR = 11.62, 95% CI, 3.59–37.59), multiple sexual partners (OR = 3.39, 95% CI, 1.23–9.38), blood transfusion (OR = 13.74, 95% CI, 4.22–44.71), surgeries (OR = 3.02, 95% CI, 1.03–8.83), alcoholism (OR = 6.94, 95% CI, 2.32–20.75), mouth-to-mouth kissing (p = 0.001 ), and contact with HBV patient (OR = 4.14, 95% CI, 1.01–17.06). People without prior knowledge of HBV infection were more infected. Conclusion . This study reaffirms the endemicity of HBV in a part of sub-Saharan African country. Public health practitioners should focus attention on apparently healthy patients in developing countries. We suggest inclusion of HBsAg screening for patients coming for routine hospital care.